The cost of access: Examining asset-based barriers to formal agricultural markets in rural Jozini, South Africa - Ngubane, Andile; Masuku, Mfundo Mandla (Asian Journal of Agriculture and Rural Development, 2025)
Small-scale rural farmers in South Africa encounter persistent barriers to formal market participation, despite the potential of these markets to enhance income stability, agricultural development, and food security. This study investigates the structural and institutional constraints that limit small-scale farmers’ engagement with formal value chains, with particular emphasis on the role of asset availability and management. Employing the Asset Vulnerability Analytical Framework (AVAF), the research examines how deficiencies in critical assets (physical, financial, and institutional) contribute to farmers’ marginalization. A qualitative methodology was adopted, drawing on data from six focus group discussions with small-scale farmers and seven semi-structured interviews with key informants in Jozini, KwaZulu-Natal. This approach enabled a comprehensive understanding of both farmers’ experiential realities and institutional perspectives on market access. Findings reveal that farmers’ capacity to meet formal market demands is constrained by logistical challenges, market saturation, limited organizational capacity, and inadequate transportation. Furthermore, insufficient institutional support and the absence of cooperative structures undermine farmers’ bargaining power and market preparedness. The study highlights the necessity of a multidimensional strategy that prioritizes infrastructure development, institutional support, and capacity building to facilitate the integration of small-scale farmers into formal markets and to enhance their long-term livelihood security and resilience.